SUPERIOR RESPONSIBILITY FOR INTERNATIONAL CRIMES IN ETHIOPIAN CRIMINAL LAW - Ezedin Fedlu Nuri (International Journal of Innovations in Engineering Research and Technology, 2023)
This study aimed to assess the status of Superior/command responsibility in Ethiopian criminal law. For this purpose the international criminal law on the issue of SR, comparative criminal law, international as well as domestic cases and the Ethiopian criminal law are assessed. The study employed a doctrinal as well as qualitative approach. The assessments of the study show that: SR is a form of criminal responsibility that addresses the culpability of superiors who fail to prevent or punish their subordinates committing international crimes. It has been developed through customary international law. The justification for the development of SR in international criminal law was that low-level officials or military personnel often commit crimes because their superiors failed to prevent or repress them. The doctrine aimed at promoting compliance with international human rights law by obligating Superiors to curb the criminal acts of subordinates. This in turn promotes effective and merit based leadership. However, the doctrine of SR is not established in Ethiopian criminal law. It is not also practiced as customary international law. The absence of the doctrine of SR in the Ethiopian criminal law, cosseted the country a lot because while violation of human rights and commission of international crimes witnessed, no superior has been held criminally responsible based on the principles and elements of SR. All in all, as the study show, in the case of Ethiopia there is a legal gap on the issue of SR.